Au@Co2P core/shell nanoparticles as a nano-electrocatalyst for enhancing the oxygen evolution reaction. Issue 70 (10th December 2019) - Zhang, Xiaofang; Shan, Aixian; Duan, Sibin; Zhao, Haofei; Wang, Rongming; Lau, Woon-Ming
Abstract : Au@Co2 P core/shell nanoparticles were designed and prepared to improve the oxygen evolution reaction performance. Abstract : Core/shell nanoparticles (NPs) of Au@Co2 P, each comprising a Au core with a Co2 P shell, were prepared, and shown to efficiently catalyze the oxygen evolution reaction (OER). In particular, Au@Co2 P has a small overpotential of 321 mV at 10 mA cm −2 in 1 M KOH aqueous solution at room temperature, which is about 95 mV less than pure Co2 P. More importantly, the Tafel slope of Au@Co2 P, at 57 mV dec −1, is 44 mV dec −1 lower than that of Co2 P. Hence, Au@Co2 P outperforms Co2 P drastically in practical production when a high current density is required.